Strategi Nafkah Petani Tomat (Lycopersicom Esculentum Mill) Di Desa Lowian Kecamatan Maesaan Kabupaten Minahasa Selatan - Eman, Falentina Estrela; Manginsela , Elsje Pauline; Benu, Noortje Marselianie (AGRI-SOSIOEKONOMI, 2023)
This study was conducted to determine and analyze the livelihood strategies of tomato farmers in Lowian Village, Maesaan District, South Minahasa Regency, North Sulawesi Province. The research was conducted from November 2022 to February 2023. The research location is in Lowian Village, Maesaan District, South Minahasa Regency. This research method used primary data and secondary data. Primary data was obtained by conducting direct interviews with tomato farmers in Lowian Village, Maesaan District. Secondary data were obtained from relevant agencies or institutions involved in the research. The selection of research samples is purposively (puporsive sampling) where the sample is tomato farmers who have their own land, the main source of farmer income is tomato farming and at least 5 years of growing tomatoes in Lowian Village, Maesaan District, South Minahasa Regency. The population of tomato farmers in Lowian Village amounted to 10 people and the sample was 3 farmers who were willing to be interviewed further. Analyzing livelihood strategies using descriptive qualitative analysis. The results showed that the livelihood strategy used by tomato farmers in Lowian Village, Maesaan Subdistrict in the accumulation strategy, respondent farmers applied the accumulation strategy to obtain agricultural land from initially only having narrow land by applying the accumulation strategy farmers can buy land and obtain large land. Consolidation strategy, respondent farmers apply a consolidation strategy by buying land close to the house and land with one another close together so as to form a large expanse that can facilitate farmers in cultivating farming. Intesification strategies are carried out by respondent farmers by planting several types of plants, carrying out maintenance and providing fertilizers.